Field Measurement Results on the Presence of Rogue Base Stations (Fake BTS) in Urban Areas - Pardede, Mahadi (West Science Information System and Technology, 2025)
This research examines the presence and technical characteristics of rogue base stations (illicit BTS) through empirical field assessments conducted in densely populated urban environments. By employing a spectrum analyzer alongside the G-NetTrack application across frequency ranges extending from 900 to 2300 MHz, the investigation revealed signal anomalies that are suggestive of unauthorized base station operations. The signals that were detected displayed abnormal intensities coupled with variable stability, abrupt shifts from 4G/5G networks to 2G networks, and discrepancies in cell ID and network identity parameters (MCC, MNC, LAC). These attributes imply coerced connections to illegitimate transmitters. The rogue BTS units were predominantly located in close proximity to governmental offices, commercial hubs, and public venues, thereby indicating a potentially strategic deployment approach. The results underscore the critical necessity for the implementation of early detection systems and inter-agency cooperation to alleviate the risks associated with communication interception. By furnishing technical indicators and empirical measurement data, this study contributes to the advancement of network security frameworks and informs policy formulation aimed at safeguarding cellular infrastructure.